Influence of Technological Factors on Fatigue Properties of Steel Sheets - Marian Bursak; Otakar Bokuvka (Communications - Scientific letters of the University of Zilina, 2006)
Treatment technology can influence the fatigue process positively or negatively. The paper analyzes the influence of cold levelling of strips from coils of steel grade E 700 TS (Re 700 MPa) on the fatigue crack initiation and the fatigue limit under one-sided bending (R 0.1). It indicates a positive effect on the above-mentioned characteristics if strips are loaded under one-sided bending from the side where residual compressive stress is formed during levelling.By blasting a sheet made of steel grade 11 375.1, the fatigue limit under symmetrical flat bending was increased due to the hardening and formation of residual compressive stress. The paper also indicates risks connected with blasting, influencing the fatigue life.